Perilaku Herding pada Jakarta Islamic Index (JII) - Alifa Jauzaa; Asri Khayati; Axel Giovanni (Jurnal Pasar Modal dan Bisnis, 2022)
Herding behavior is the attitude of investors who do not take into account the available information and prefer to follow the decisions of other investors in making decisions. Herding can occur when investors tell themselves and are more sure of other investors without careful consideration. Herding behavior is measured by looking at the relationship between the market portfolio (Rmt2) and Cross Sectional Absolute Deviation (CSAD). This study aims to identify evidence of herding behavior on the JII stock index. This study uses the JII index (Jakarta Islamic Index) with 29 companies selected as samples. The research period is monthly from April 2020 to March 2021. The results show that stock market investors in the Jakarta Islamic Index do not show a significant relationship between CSAD and market returns in each quantile or in other words. The Jakarta Islamic Index does not show any symptoms of herding behavior in every market condition (low return, normal, and high return). This can be proven by the magnitude of the probability value of the y2 variable which is above 0.05 in each analyzed market condition.